1 - Wita Rosiana; Ratna Dumilah (International Journal of Multidisciplinary Research and Literature, 2023)
This study aims to determine the Work Environment and Discipline-Based Performance of Siloam Hospitals Kebon Jeruk West Jakarta General Affair (GA) Employees. This study uses quantitative research. The population in this study were all General Affair (GA) employees at Siloam Hospitals Kebon Jeruk West Jakarta with a sampling of 80 respondents. Collecting data by distributing questionnaires. Methods of data analysis using simple linear regression test, multiple linear regression, correlation coefficient, coefficient of determination, partial t test and simultaneous F test. The results showed that: The work environment has a positive and significant effect on the performance of General Affair (GA) employees at Siloam Hospitals Kebon Jeruk, West Jakarta. This can be proven from the simple linear regression equation Y = 10.155 + 0.767 X1. The correlation value is 0.807 (very strong). The coefficient of determination is 65.1% The tcount is 6.201 > ttable 6.007 with a significance of 0.000 <0.05. Work discipline has a positive and significant effect on employee performance for General Affair (GA) employees at Siloam Hospitals Kebon Jeruk, West Jakarta, this can be proven from the simple linear equation Y = 4.469 + 0.877 X2 . Correlation value of 0.871 (very strong). The coefficient of determination is 75.9% The tcount is 17.060 > ttable 6.007 with a significance of 0.000 <0.05. Simultaneously, work environment and discipline have a positive and significant effect on employee performance at Siloam Hospitals Kebon Jeruk West Jakarta General Affair (GA) employees, this can be proven from the multiple linear regression equation Y=2.192+0.325X1+0.615X2. The correlation value is 0.899 (very strong). The Coefficient of Determination is 80.8%. Fcount value 153.975 > Ftable 3.12 with a significant level of 0.000 <0.05